2022
DOI: 10.2166/nh.2022.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multisource precipitation input for hydrological modeling in an Alpine basin: a case study from the Yellow River Source Region (China)

Abstract: Alpine basins are typically poorly gauged and inaccessible owing to the harsh prevailing environment and complex terrain. In this study, two representative satellite precipitation products (Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA) 3B42RTV7 and Integrated Multi-Satellite Retrievals for GPM (IMERG) Final Run Version 06) and two reanalysis precipitation products (China Meteorological Assimilation Driving Datasets for the SWAT model (CMADS) and Climate Forecast Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
(105 reference statements)
0
6
0
1
Order By: Relevance
“…Sun et al, 2018), regional (Bytheway et al, 2023;Hu et al, 2016;Satgé et al, 2020), national (Aksu & Akgül, 2020;Du et al, 2022;Li et al, 2022;Liu et al, 2022;Nepal et al, 2021;W. Xie et al, 2022), and basin scales (Adhikari & Behrangi, 2022;Dangol et al, 2022;Gu et al, 2022;J. Chen et al, 2020;Khadka et al, 2022;Kumar et al, 2021;.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Sun et al, 2018), regional (Bytheway et al, 2023;Hu et al, 2016;Satgé et al, 2020), national (Aksu & Akgül, 2020;Du et al, 2022;Li et al, 2022;Liu et al, 2022;Nepal et al, 2021;W. Xie et al, 2022), and basin scales (Adhikari & Behrangi, 2022;Dangol et al, 2022;Gu et al, 2022;J. Chen et al, 2020;Khadka et al, 2022;Kumar et al, 2021;.…”
Section: Introductionunclassified
“…Until now, many evaluation studies of such datasets have been conducted at global (Beck et al., 2017; Derin et al., 2019; Li et al., 2021; Q. Sun et al., 2018), regional (Bytheway et al., 2023; Hu et al., 2016; Satgé et al., 2020), national (Aksu & Akgül, 2020; Y. Chen et al., 2021; Du et al., 2022; Li et al., 2022; Liu et al., 2022; Nepal et al., 2021; Sharma, Khadka, et al., 2020; W. Xie et al., 2022), and basin scales (Adhikari & Behrangi, 2022; Dangol et al., 2022; Gu et al., 2022; J. Chen et al., 2020; Khadka et al., 2022; Kumar et al., 2021; W. Wang et al., 2020). Most of them have uncovered uncertainties in the measurements, particularly when dealing with complex terrain.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the hydrological simulation at the basin scale in alpine regions is frequently performed using physically‐based models such as the CRHM (DeBeer & Pomeroy, 2017; J. Zhou et al., 2014), SWAT (Gu et al., 2022; K. Li, Wang, et al., 2021; Zeng et al., 2022), VIC(S. Li, Wang, et al., 2021; Y. Wang, Zhang, et al., 2020), Alpine3D (Brauchli et al., 2017), GBEHM (B. Gao, Qin, et al., 2016), CoupModel (J. Zhou et al., 2013), WaSiM(A. Sun et al., 2020), Topkapi‐ETH (Fatichi et al., 2015), and HGS (Thornton et al., 2022), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the hydrological simulation at the basin scale in alpine regions is frequently performed using physically-based models such as the CRHM (DeBeer & Pomeroy, 2017; J. Zhou et al, 2014), SWAT (Gu et al, 2022;K. Li, Wang, et al, 2021;Zeng et al, 2022), VIC(S. Li, Wang, et al, 2021;Y.…”
mentioning
confidence: 99%
“…Due to its nonlinearity, even small variations in input can lead to substantial changes in output. Previous studies have demonstrated how alterations in precipitation can have significant impacts on streamflow estimation [18][19][20][21]. Moreover, the hydrological modeling process uncertainty raises concerns from the simplified or incorrect representation of the hydrological system.…”
Section: Introductionmentioning
confidence: 99%